11 Tissue vaporization mechanism in photoselective vaporization of the prostate based on EDFA. (March 2019) - Hao, ZQ; Zhan, WD; Tang, YF; Wang, YJ
Abstract : Background: To develop a more efficient scheme in photoselective vaporization of the prostate (PVP) with fewer side effects, as well as to determine the critical time of tissue coagulation or vaporization and the degree of thermal damage of the tissue, the tissue vaporization mechanism in photoselective vaporization of the prostate based on EDFA was analyzed. Methods: By comparing the laser vaporization effect of animal liver tissue, muscle tissue and prostate tissue, a laser operation scheme based on EDFA was proposed. The 1064 nm laser is used as the light source, whose power is amplified by EDFA, and the 532 nm laser is obtained by frequency doubling of KTP, which has higher vaporization efficiency and less thermal damage in PVP operation. Results: When the output power of the system is 48.9 W, the frequency is 50 Hz, the pulse width is 5 ms, and the action time is 10 s. In dog prostate samples, the vaporization pit with diameters of 2.0 mm and 3.5 mm, respectively, are produced in aqueous and air conditions, and the thermal damage thickness is 0.4 mm and 0.8 mm. Conclusion: The experimental results show that the establishment of the system is of great significance for the study of the tissue vaporization mechanism and provides a valuable reference for further improvement of PVP operation. Acknowledgements: Supported by a project from Jilin Science and Technology Department (Project No.20170204079GX).